2017
DOI: 10.1101/157925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Questioning unexpected CRISPR off-target mutations in vivo

Abstract: To the Editor: Recently, Schaefer et al. 1 reported that whole genome sequencing (WGS) of two Cas9-treated, gene-corrected mice and a wild-type control mouse unveiled 1,397 singlenucleotide variations (SNVs) and 117 small insertions and deletions (indels) present commonly in the two Cas9-treated mice "but absent in the uncorrected control" and from a database of mouse SNVs and indels. There was essentially no sequence homology between the on-target site and these SNVs and indel sites, most of which lacked a pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Lastly, we identified a heritable T to A substitution which led to a single nucleotide variation (SNV) and here results in a premature stop codon ( Figure 3B and 3C ). This occurs when a single bp deletion is followed by a single bp insertion, an event very rarely observed for CRISPR/Cas9 ( Kim et al 2017 ). In conclusion, the pDE-Cas9 vectors allow for efficient and inheritable genome editing in Arabidopsis with the possibility of producing transgene free homo-allelic mutants in the T2 generation.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we identified a heritable T to A substitution which led to a single nucleotide variation (SNV) and here results in a premature stop codon ( Figure 3B and 3C ). This occurs when a single bp deletion is followed by a single bp insertion, an event very rarely observed for CRISPR/Cas9 ( Kim et al 2017 ). In conclusion, the pDE-Cas9 vectors allow for efficient and inheritable genome editing in Arabidopsis with the possibility of producing transgene free homo-allelic mutants in the T2 generation.…”
Section: Resultsmentioning
confidence: 99%
“…Our statistical test, however, indicates a significant difference between the heterozygosity of them (p-value=0; Supplementary Notes), proving that the overall derived mutation pattern in Study_1 is not germline-like. Note that Lareau et al and Kim et al 4,6 recently demonstrated that the two CRISPR-Cas9 treated mice (F03, F05) in Study_1 are actually more closely related to each other genetically than to the control mouse, proving that these mutations are most likely preexisting variants. Our analysis result further presented that there are unusual SNVs arose in Study_1 combined with pre-existing variants, and the overall mutation pattern in vivo are not germline-like.…”
Section: Snvsmentioning
confidence: 93%
“…79 In addition to the viewpoint from Lareau et al, there are some other researchers questioning Schaefer et al's point of view. Kim et al 80 and Wilson et al, 81 for instance, both think that the observed variants in Schaefer et al's experiments are much more proper to be explained by the differences in the genetic background of the mice rather than mutations caused by Cas9. Thus, this issue is currently under drastic controversy and more efforts are needed to clarify it.…”
Section: Off-target Effect and Solutionsmentioning
confidence: 97%